ANALISIS KOALISI PARTAI PKB DALAM PEMENANGAN PUTRA KIAI DI PUSARAN KEKUASAAN - Muhammad Izzudin Haq (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
This research aims to describe how the coalition of the National Awakening Party (PKB) contributed to the victory of a cleric's son in the Sidoarjo Regional Elections (Pilkada). The general objective of this study is to analyze how political party coalitions occurred during the 2020 Pilkada in Sidoarjo. To obtain data, the researcher employed library research, utilizing literature studies that did not require direct interaction with respondents or fieldwork. The researcher collected various necessary research data from literary sources or documents such as papers or previous research results related to electoral and regional elections participation in Sidoarjo. The research findings indicate several factors that led to PKB's success in the Sidoarjo Pilkada. First, the Political Party Coalition Factor: The coalition with political parties, particularly Nasdem and PSI, provided significant political support and a voter base for the Ahmad Muhdlor and Subandi ticket. PKB's negotiation strategy in forming the coalition played a crucial role in garnering support and votes. Second, the Political Participation Factor: Active political participation by the Ahmad Muhdlor and Subandi ticket, involving understanding important political issues for the community and responding to genuine aspirations for change, had a positive impact in winning voters' hearts. Their ability to articulate the needs and desires of the community through political campaigns also contributed to their victory. Third, the Modalities Factor: The modalities possessed by this ticket, including social capital such as connections with NU (Nahdlatul Ulama) and social organizations, cultural capital such as education and organizational experience, as well as economic capital acquired from campaign donations, played a significant role in building support and designing effective campaign strategies. The combination of these factors aided the PKB coalition in achieving victory in the 2020 Sidoarjo Pilkada. Cooperation within the coalition, the ability to understand relevant political issues, active political participation, and the utilization of existing modalities all contributed to creating public support and trust that enabled the Ahmad Muhdlor and Subandi ticket to succeed in the election.